Literature Review Chatbot E-Commerce - Azzah, Reva Aurellia; Mardhiah, Zahidah Fathia; Mubarok, Ahmad Kusma Rizkqi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines five key aspects that constitute the main focus of the research: customer service efficiency, system integration and automation, conversational humanization, user trust and satisfaction, as well as ethical and data security issues. Through this discussion, the study seeks to understand how AI-powered chatbots not only enhance business performance but also transform human–technology interaction within the context of modern e-commerce. This research employs a literature review approach by systematically examining previous studies relevant to the research focus. The findings indicate that, based on an analysis of 115 publications published between 2019 and 2025, AI chatbots have emerged as one of the primary drivers of digital transformation in e-commerce. This technology significantly improves operational efficiency and customer service quality while simultaneously strengthening the emotional relationship between users and brands. The rapid growth of research since 2022 demonstrates that chatbots now occupy a strategic position in shaping online shopping experiences. The combination of task-oriented and conversation-oriented chatbots has been shown to produce higher levels of user satisfaction and conversion rates. Nevertheless, anthropomorphic features must be applied cautiously to avoid the uncanny valley effect, which may reduce user comfort. Despite their substantial potential, several critical challenges remain, including data privacy concerns, the digital divide, and the need for adaptation to diverse cultural contexts. The future success of chatbot implementation will largely depend on the ability of developers and companies to balance technological sophistication, psychological understanding of users, and ethical responsibility.